Comment on Effects of Insufficient Sleep on Myopia in Children: A Systematic Review and Meta-Analysis [Letter] - Sun H; Zheng Z; Shao X (Nature and Science of Sleep)
Haomin Sun,1,* Zicheng Zheng,2,* Xiaomei Shao1 1The Third Clinical Medical College of Zhejiang Chinese Medical University, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, 310053, People’s Republic of China; 2Ophthalmology Department, The Affiliated Municipal Hospital of Taizhou University, Taizhou, 318000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaomei Shao, The Third Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Binjiang District, Hangzhou, Zhejiang, People’s Republic of China, Email shaoxiaomei@zcmu.edu.cn